Datura stramonium poisoning: a case report and review of the literature - Korkmaz, Muhammet Furkan; Bostancı, Muharrem; Onur, Hatice; Çağan, Eren (The European Research Journal, 2019)
Datura stramonium is a widespread annual, leafy herbaceous plant that is a powerful hallucinogen. It can cause severe anticholinergic poisoning after inappropriate and unconsciously usage. We would like to present an approach, accompanied by literature, to the poisoning case for a 6-year-old child who initially presented with altered mental status, abnormal/incoherent speech and agitation, and had an only response to physostigmine. It is essential to consider anticholinergic plant-based ingestions in the differential diagnosis of children presenting with altered mental state, hallucination, and agitation. Health care workers and parents should be aware of toxicities and potential risks of these plants.